Cholecystostomy as Bridge to Surgery and as Definitive Treatment or Acute Cholecystectomy in Patients with Acute Cholecystitis - Agnieszka Popowicz; Lars Lundell; Peter Gerber; Ulf Gustafsson; Emil Pieniowski; Helen Sinabulya; Krister Sjödahl; Andrianos Tsekrekos; Gabriel Sandblom (Gastroenterology Research and Practice)
Purpose. Percutaneous cholecystostomy (PC) has increasingly been used as bridge to surgery as well as sole treatment for patients with acute cholecystitis (AC). The aim of the study was to assess the outcome after PC compared to acute cholecystectomy in patients with AC. Methods. A review of medical records was performed on all patients residing in Stockholm County treated for AC in the years 2003 and 2008. Results. In 2003 and 2008 altogether 799 and 833 patients were admitted for AC. The number of patients treated with PC was 21/799 (2.6%) in 2003 and 50/833 (6.0%) in 2008. The complication rate (Clavien-Dindo ≥ 2) was 4/71 (5.6%) after PC and 135/736 (18.3%) after acute cholecystectomy. Mean (standard deviation) hospital stay was 11.4 (10.5) days for patients treated with PC and 5.1 (4.3) days for patients undergoing acute cholecystectomy. After adjusting for age, gender, Charlson comorbidity index, and degree of cholecystitis, the hospital stay was significantly longer for patients treated with PC than for those undergoing acute cholecystectomy (P<0.001) but the risk for intervention-related complications was found to be significantly lower (P=0.001) in the PC group. Conclusion. PC can be performed with few serious complications, albeit with a longer hospital stay.